Human behavior and the social environment, micro level : individuals and families - Van Wormer, Katherine S. (OXford University Press, 2007)
"Human Behavior and the Social Environment, Micro Level explores the nuances of the biological, psychological, cultural, and spiritual dimensions of our social lives.